﻿Weight management strategies and food supplement intake among Bulgarian adults: results of a national survey - Radiana Staynova; Vesselina Yanachkova (Pensoft Publishers, 2023)
The number of overweight and obese people has dramatically risen in the last two decades and has become one of the most serious health concerns. This study aimed to assess the use of food supplements as aids in reducing body weight and different approaches for weight management practised by Bulgarian adults. A cross-sectional, questionnaire-based online survey was conducted between December 2019 and February 2020. A total of 508 adults completed the survey. According to study participants, the Internet was the most used source of weight reduction information (66.9%). One hundred and seventy-two adults (33.9%) have sought weight-loss advice from a personal trainer/fitness instructor, and only 12.6% (n = 64) have consulted with a physician. More than half of the respondents (n = 288, 56.7%) reported food supplement use to maintain weight. The majority of the consumers were female (76.4%, p < 0.001) and adults with higher education (89.9%, p < 0.001). The main reasons for food supplement intake were individual research on the Internet (43%), advice from a personal trainer/fitness instructor (23.6%), and a recommendation from a healthcare provider (22.2%). With the increasing rates of overweight and obesity, food supplements are becoming a popular weight-loss approach, which is confirmed by our findings.